ANALISIS PELAKSANAAN DINAS JAGA DI AHTS AMBER UNTUK MENGHINDARI BAHAYA TUBRUKAN PADA SAAT BERLAYAR - Muh. Fathir Muar; Hadi Setiawan; Indra Farman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of watchkeeping duty on AHTS AMBER in order to prevent the risk of collision during voyages. A qualitative descriptive approach was used, with data collected through interviews with ship officers, direct field observation, and document review during sea practice on board. The findings show that watchkeeping practice has not been fully optimal according to STCW 1978 as amended in 2010, particularly regarding crew discipline in handing over the watch, coordination among watch personnel, and understanding of safety procedures. Navigational aids such as Radar and ARPA have also not been fully utilized to support collision avoidance, mainly because several officers were not yet familiar with the newer radar unit. These conditions are influenced by limited crew skill, insufficient understanding of standard operating procedures, and inadequate oversight from ship management. Improved training and familiarization, consistent enforcement of standard operating procedures, and better use of modern navigational equipment are recommended to increase vigilance and early hazard detection, so that the risk of collision can be minimized.